Methodological issues in international entrepreneurship research - Coviello, Nicole E; Jones, Marian V (Journal of Business Venturing, 2004)
Empirical research in the emerging field of international entrepreneurship (IE) is assessed to provide insight as to the ‘state of the art’ of IE methodologies. Fifty-five articles were systematically analyzed focusing on time frame and research context, sample characteristics, data collection/analysis procedures, and equivalence issues. Results indicate both strengths and weaknesses in IE methods. The authors present implications for developing a unifying methodological direction in the field and the evolution of a truly multidisciplinary approach. They also outline the need for dynamic research designs that integrate positivist with interpretivist methodologies and incorporate time as a key dimension. Finally, they discuss the need for better IE sampling frames and call for more effort in establishing and reporting equivalence in cross-national studies.